(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1923)
One of the so-called otter or beaver traps was discovered during peat digging on the Moss of Auquharney, Aberdeenshire, together with three fragments of a stout stick, apparently used in connection with the trap. This trap appears to be the only one of its kind hitherto discovered in Scotland. Most writers have regarded them as traps to catch otters, beavers, wild-fowl, fish, etc., but no very satisfactory explanation of their mode of use has been given, while others have considered them to be machines for making peat blocks, musical instruments, models of boats, etc. The writer is of opinion that these traps were constructed for the capture of large animals, such as deer, and suggests that their remains are only found in peat because in other situations they have perished.